Analysis Strategies in Completing Local Culture-based Mathematics Assessment with PISA Standard - Widiawati, Ayu Maulinda; Ummah, Siti Khoiruli; Effendi, Moh. Mahfud (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aimed to determine the learning strategies used by students in working on PISA assessments characterized by local culture. The method used in this study was descriptive using qualitative data. The results of the study showed that the rehearsal strategy and organization strategy were used by all class classifications of high, medium and low classes. However, in the high class, the rehearsal strategy was used in all students while in the low class the rehearsal strategy was only used in certain numbers. For the elaboration strategy it only appears in the medium class. Whereas metacognitive strategy is only seen in a low class. In terms of local culture, after working on the questions given, there were previously unknown tourism which later became known such as the Makam Mbah Batu, Kampung Wisata Kungkuk, Arboretum, etc. In addition, they claimed to be more interested in visiting existing tourism, especially tourism that they just found out from the assessment.